Conducta obstétrica en paciente primigesta de 28 años con miomatosis uterina. - Blacio Aguilar, María Estefanía (2021)
Uterine myomatosis is a condition that has become common to detect in women, these tumors are often the main cause of fertility problems. They also represent a risk factor for ongoing pregnancies. The present clinical case study refers to a 28-year-old female patient who presented for consultation due to moderate transvaginal bleeding, detecting a myoma which was excised. The patient indicates that she was pregnant, however at the next medical check-up, the clinical examination indicates that her pregnancy was spontaneously interrupted. There is a high relationship between the presence of fibroids and the termination of pregnancy. It is known to professionals that these are a cause of infertility. Reason why it is necessary to carry out tests of this type to identify. When abortions due to myomatosis occur, the most advisable thing for patients is to implement a contraceptive plan in order to provide adequate treatment prior to a state of pregnancy.